Chapter Una fiscalità europea per uno sviluppo equo e sostenibile - Majocchi, Alberto (Studi e saggi, 2022)
The dramatic health emergency that has hit Europe has put the issue of a thorough reform of the European budget financing system back on the political discussion table, in order to support the expenditure required to cope with the new tasks that are increasingly expected to be assigned to the Union. The ensuing debate concerns both the nature of the new resources and the new tasks that are to be assigned to the European budget. And it also concerns how the distribution of resources between the different levels of government is to be defined. European taxation has so far been based, without any particular discussion, on the principle that taxation power remains a competence of the Member States. However, the impetus induced by climate change and the need to find resources to combat it is changing the situation. The idea of introducing a carbon tax at European level could be the embryo of a fiscal autonomy of the Union.